Test houses for roof thermal performance testing / Badrul Hisham Mohd Noor, Azni Zain-Ahmed and Nasharudin Sulaiman - Mohd Noor, Badrul Hisham; Ahmed, Azni Zain; Sulaiman, Nasharudin (2008)
Two test houses were built at a location within UiTM Pahang, Jengka campus. The houses were made of plywood with cement bases and 5° single pitch metal deck roofs. The houses, H1 and H2, were built in an open area and at a distance to each other; and in the East- West direction to minimize wind and shading effect. Temperature sensors were attached to the top surface of the roofs; and also on the inside surface of the radiant barrier for both houses to monitor their temperature profiles. Data was collected for a period of time using a computer placed in one of the houses. From the data, it was found that both houses showed similar temperature profiles except that the house, H2, containing the computer, is consistently hotter on average by O.62°C on the inside and by O.32°C on the outside. A correction to the H2 temperature is made by subtracting the respective average temperature difference values. The corrected temperatures of H2 were then compared to the temperatures of H1 and their differences were found to be statistically insignificant. This result proved that both houses were thermally the same within the limits of uncertainties. Consequently, the test houses could be used for further roof testing purposes with one of the houses to serve as control.